2009
DOI: 10.1007/s00403-009-0982-2
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Mycobacterium tuberculosis specific immune responses in patients with untreated psoriasis living in a tuberculosis endemic area

Abstract: Tuberculosis has emerged as a major concern in patients with immuno-mediated diseases, including psoriasis, undergoing treatment with biologicals. However, it is not known whether the chronically activated immune system of psoriasis patients interferes with their Mycobacterium tuberculosis (Mtb)-specific immunity, especially in tuberculosis-endemic areas like Brazil. We evaluated T-cell responses to a Mtb lysate and to the recombinant Mtb proteins ESAT-6 and Ag85B of tuberculin skin test (TST) positive and TST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 29 publications
2
25
0
2
Order By: Relevance
“…33 These results suggested that aberrant T-cell response to M tuberculosis antigen in severe psoriasis may lead to reactivation of latent TB. Long-term use of systemic immunosuppressive drugs may partly explain the association between TB and psoriasis.…”
Section: J Am Acad Dermatolmentioning
confidence: 97%
“…33 These results suggested that aberrant T-cell response to M tuberculosis antigen in severe psoriasis may lead to reactivation of latent TB. Long-term use of systemic immunosuppressive drugs may partly explain the association between TB and psoriasis.…”
Section: J Am Acad Dermatolmentioning
confidence: 97%
“…PBMC were stimulated with the mitogen phytohaemagglutinin (PHA), the superantigen enterotoxin B (SEB), from Staphylococcus aureus, a cytomegalovirus (CMV) lysate, and M. tuberculosis (Mtb) antigens, and the lymphocyte aetivation was evaluated by enzyme-linked immunosorbent spot assay (ELISpot) for enumeration of IFN-y-secreting cells, enzyme-linked immunoassay (ELISA) for detection of seereted IFN-y, and by [^H] thymidine incorporation for lymphocyte proliferation measurement. These assays were selected as in previous studies (12) because the ELISpot deteets T cells that, after a few hours (overnight) exposure to antigens or other stimuli, secrete IFN-y, a feature of effector memory T eells, while the IFN-y ELISA and lymphocyte proliferation assay preferentially measure functions of central memory T eells, which need several days after activation to undergo clonal expansion or secrete large amounts of cytokines.…”
Section: Peripheral Blood Mononuclear Cells Isolation and Storagementioning
confidence: 99%
“…TNF participation in the pathogenesis of psoriasis and stabilization of the granuloma in tuberculosis supports the hypothesis that anti-TNF therapy promotes reactivation of LTBI. 18 Between 1998 and 2002, the Adverse Event Reporting System of the FDA found 716 granulomatous infections associated with anti-TNF therapies, including tuberculosis, histoplasmosis, aspergillosis, listeriosis and cryptococcosis. Patients who developed tuberculosis during the anti-TNF therapy presented inability to form a granuloma, prominent interstitial fibrosis and lymph node inflammation.…”
Section: Anti-tnf Action and Tuberculosis Triggeringmentioning
confidence: 99%
“…When the memory function of T cells was tested, by means of a study in vitro via measuring the production of INF-γ, a decrease in this response was also observed, suggesting a characteristic similar to that presented by patients with rheumatoid arthritis. 18 The anti-M. tuberculosis reaction in these individuals is probably affected, especially if the housing area is endemic for infection with this bacillus. Therefore, one can expect that there is a higher incidence of false negative results for the PPD test in these patients compared with the population not affected by the disease, further distancing this test from being recognized as the gold standard in diagnosing latent tuberculosis.…”
Section: Psoriasis Patient's Behavior In Relation To the Tuberculin Smentioning
confidence: 99%